1, 3-Oxazines as BACE1 and/or BACE2 inhibitors: a patent evaluation (WO2012156284). (August 2013) - Gilbert, Eric J
Abstract : This patent review covers the contents of Hoffman-La Roche and Siena Biotech's patent application WO2012156284 titled '1, 3-Oxazines as BACE1 and/or BACE2 Inhibitors.' Beta-site amyloid precursor protein-converting enzyme (BACE1) and BACE2 activities are reported to support the claimed compounds' use as therapeutics for Alzheimer's disease and type II diabetes, respectively. A common core motif of the claimed compounds is the six-membered 1, 3-oxazine system. To gain access to the S3 and S3 subpocket of the BACE1 active site, various linkers are described including nitrogen- and oxygen-based, aryl, and amide-based linkers. Of the 65 compounds claimed, 6 had IC50s less than 100 nM in the BACE1 cell assay. Cellular BACE2 inhibition data are reported for 20 compounds with 2 under 100 nM.